Immune Reconstitution Inflammatory Syndrome Occurring in a Kidney Transplant Patient with Extrapulmonary Tuberculosis - Jose Iglesias; Kandria Jumil Ledesma; Paul J. Couto; Jessie Liu (Case Reports in Transplantation)
Tuberculosis (TB) occurring in solid organ transplantation (SOT) is associated with significant morbidity and mortality usually due to delays in diagnosis, drug toxicity encountered with antimycobacterial therapy, and drug-drug interactions. TB in SOT patients may mimic other infectious and noninfectious posttransplant complications such as posttransplant lymphoproliferative disorder (PTLD) and systemic cytomegalovirus infection. Immune reconstitution inflammatory syndrome (IRIS) is a host response resulting in paradoxical worsening of an infectious disease which occurs after the employment of effective therapy and reversal of an immunosuppressed state. We describe the development of immune reconstitution inflammatory syndrome (IRIS), a unique complication occurring during the treatment of extrapulmonary tuberculosis occurring after transplant which resulted from decreasing immunosuppression in a patient who received Alemtuzumab induction therapy. Although (IRIS) has been originally described in HIV/AIDS patients receiving highly active antiretroviral therapy (HAART), solid organ transplant recipients with diagnosed or occult TB whose immune system may undergo immune reconstitution during their posttransplant course represent a new high risk group.